(3TQM GdeYGdes - (3GdeGRfOQGfj, GdCUagGfj, MSGe GdOjf, eMeO UGdM Hf CMeO, J (B1081 (3g`s
(3ChdgG (B:s
(3fMeOc Gddg jG ef NdbfG (B... (3Ef HYV NdGfj deG QCi eG YdbJg Ydi eYGde GdOjf dDdDG efKhQG SCdfj Cf CMQQ dge ahGFOg hCfXe dge aQGFOI hCeQ Ydjg eQhQG aCLHJ eSDhdge (B...s
(3BNQgG (B:s
.. (3dG jbGd aj bUU OdGdI Ydi bOQI GdHTQ Ydi GdEYLGR MjK cGf cKjQG efgG CcKQ ef KdGK BjGJ dMcGjI dbeGf hMcGjI eDef Bd aQYhf dCfG fbhd djS GdHdGZI HeLQO (B.. (3hbY GdaQGZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI(B1 (1956)s
(3GdPQjYI (B14\1787s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs